Photo-Electrical Tandem of Modulated Polyvinyl Alcohol Based Plasticized Solid Polymer Electrolyte Nanocomposite Films: Effect of Propylene Carbonate Contents - Al-Gunaid, Murad Q. A.; Ahmed, Waled Abdo; dhif-Allah, Mohammed. A.; Al-Ostoot, Fares H. (Thamar University Journal of Natural & Applied Sciences, 2023)
Plasticized solid polymeric electrolyte nanocomposites based on polyvinyl alcohol (PVA) incorporating Cs2CuO2 nanoparticles (NPs), electrolyte salt (LiClO4) and plasticizer (PC) were prepared via solution casting technique. The dynamic light-scattering histogram revealed that the prepared Cs2CuO2 NPs have a size in the range of 80-120 nm. The interaction between different components in PVA/Cs2CuO2/LiClO4-PC films (plasticized PVA-SPEs) were probed by FTIR, while the surface and structure were evaluated by SEM and XRD, which indicate to amorphous nature of plasticized PVA-SPEs. The thermal behavior of films was measured via TGA, where a partial decrease in the thermal stability of films was noticed with an increase of PC content in the PVA-SPEs. The highest conductivity achieved is 9.56X10-5 S/cm for PVA-SPEs containing 8wt% PC at 298K. The plasticized PVA-SPEs exhibited higher specific capacitance by two folds and photovoltaic efficiency by three folds compared to pure PVA matrix.